STUDENT ORGANIZATION PERFORMANCE IN TERMS OF WORK COORDINATION AND ORGANIZATIONAL CULTURE MEDIATED BY WORK MOTIVATION - Hutapea, Martogi Daniel Rudyanto; Purnama, Eka Desy; Tecoalu, Melitina (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
In this study, researchers examine the impact of work coordination and organizational culture on student institutions' performance, employing motivation as an intervention variable and Smart PLS sample selection with 81 respondents. The purpose of this study is to determine the magnitude of the relationship between student institution performance at Jakarta's Krida Wacana Christian University and factors such as Work Coordination and Organizational Culture as an intervention variable. Qualitative data is acquired by distributing questionnaires, with validity and reliability testing employed. Data was analyzed using both qualitative and quantitative methods. The results demonstrated that work coordination and organizational culture have a favorable influence on motivation and motivation has not been able to mediate work coordination and organizational culture on the performance of Student Affairs Institutions.